Analysis Of Stock Market, Mining Commodity, Exchange Rate, And Energy Sector Stock Index Using Vector Error Correction Model: Analisis Bursa Saham, Komoditas Pertambangan, Kurs, Dan Indeks Saham Sektor Energi Menggunakan Vector Error Correction Model - Melati; Pika Silvianti; Farit Mochamad Afendi (Indonesian Journal of Statistics and Applications, 2023)
Energy Sector is one of the sectors that has a significant impact on the overall economic growth of a country. Economic growth is always linked to energy consumption, as increasing economic development leads to higher energy demand. Therefore, this study aims to analyze the factors influencing the energy sector stock index in Indonesia using Vector Error Correction Model (VECM). The data used include the energy sector stock index, crude oil prices, coal prices, gas prices, Nikkei Index, Shanghai Index, Dow Jones Index, and exchange rates from January 2021 to March 2023. VECM analysis results indicate that in the short term, crude oil prices and coal prices have a significant impact on the energy sector stock index. In the long term, significant factors are coal prices, gas prices, Nikkei Index, and exchange rates. The Impulse Response Function (IRF) analysis reveals that shocks to the energy sector stock index, crude oil prices, and coal prices can increase the energy sector stock index. Conversely, shocks to the Nikkei Index can decrease the energy sector stock index. The Forecast Error Variance Decomposition (FEVD) results demonstrate that the contributions of the energy sector stock index, crude oil prices, coal prices, and gas prices are significant in explaining the behavior of changes in the energy sector stock index.